To Assess The Co-relation of Diabetes Mellitus and Co-Morbid Tuberculosis on the leukocyte and platelet counts - Daud Aweis, Syed Azhar Syed Suleiman; Abdul Razak Mutlif (Archives of Pharmacy Practice, 2010)
Objective: The aims of this study were to assess and compare the leukocyte and platelet counts among the patients with Tuberculosis alone and co-morbid with diabetes mellitus.Methods: This was a preliminary study conducted at the respiratory clinic at public hospital, Pulau Pinang, Malaysia.Four groups were the defined retrospectively i.e patients with DM (118 patients), patient with TB (115 patients), DM-TB (76patients) and Control subjects (118 patients). Lab values like;leukocyte count, platelets, and blood glucose levels of these groups were retrieved from the medical records and then were compares to see the possible association.Results: DM patients showed quantitatively higher lymphocyte and neutrophil count than the patients with Tuberculosis (TB) alone.Conclusion: Findings demonstrated that lymphocyte and neutrophils levels were higher among diabetic patients than those with TB alone. However, thrombocytes levels were higher among the patient with TB alone and with diabetes mellitus.